Design and Construction of an Internet of Things (IoT)-Based Smart Garden System - Badriana Badriana; Putri Ramadhani; Muhammad Hidayat; Sebastian Ferdi Caras Sinuhaji; Darmeli Nasution; Aprina Br Surbakti (Karya Techno Solusindo, 2025)
The use of the Internet of Things is currently very useful for the plantation sector, especially mustard greens. The Smart Garden System is still not widely found on plantation land. Smart Garden comes from English which means garden or smart garden, which is a system design created to make work in plantations easier. The aim of making this tool is to help in managing the plants, apart from helping in managing the plants, this Smart Garden can also be used to measure the humidity/air content in the soil, because some people who are cultivating do not know/cannot distinguish which soil is good for certain crops are planted and which are not, resulting in many crops failing to harvest and being detrimental because they wither and die. So it is hoped that this smart garden system can help many farmers in maintaining soil moisture conditions and can minimize damage to plants.